Macrophyllin, a neolignan from Licaria macrophylla - Franca, Nídia Cavalcanti; Gottlieb, Otto Richard; Guilherme, José; Maia, José Guilherme Soares (Phytochemistry, 1974)
The trunk wood of Licaria macrophylla (A. C. Smith) Kosterm. (Lauraceae) contains, in addition to sitosterol, terpene (borneol) and sesquiterpene (nerolidol, elemol) alcohols, a novel neolignan, macrophyllin, for which the structure of 3-allyl-8-hydroxy-1,5-dimethoxy-7-methyl-4(or 2)-oxo-6-(3′,4′-methylenedioxy-5′-methoxyphenyl)-bicyc lo [3,2,1] oct-2(or 4)-ene is proposed. © 1974.